A case study on public participation for the conservation of a tropical of a tropical urban river. - Ming, Huey Chun; Sulaiman, Wan Nor Azmin; Abu Samah, Mohd Armi; , (Bentus, 2012)
Population pressure and land use activities in urban areas are deteriorating the health of ecologically rich tropical rivers. Despite various programs and enforcement carried out by government agencies, most river conservation projects are not sustained according to the expected objectives. Much of the blame is due to lack of public environmental awareness and participation. However, there is a lack of adequate local field data to explain this scenario. This case study was specifically conducted to evaluate the local public perception and willingness to participate on a river conservation project of an urbanized Temiang River watershed located in Peninsular Malaysia. This survey was carried out on 200 randomly selected respondents. Contrary to blame, results indicated that awareness was not the major issue; instead, it is their voluntary involvement in protecting the river. Overall, the respondents show a high willingness to be involved in the conservation program. However, factors of age, educational background, gender, income level, marital status, and residential locations determine the level of their willingness to participate.